Technological Advancement and Money Supply in Indonesia - Utami, Endah Cahyanti; Awaluddin, Muhammad (Fakultas Ekonomi dan Bisnis Universitas Mulawarman, 2024)
Technological advances in the field of non-cash payment systems, which are considered effective in their use by the public, have an impact on the increasing volume of non-cash payment transactions and the decrease in the demand for cash in the community. Where the demand for money is one of the important factors for central banks in controlling the money supply in order to maintain monetary stability in the short and long term. Therefore, this study aims to examine the influence of short-term and long-term dynamics of technological advances from non-cash payment system innovations which include Payment Instruments Using Cards (Credit and Debit), Electronic Money, and Bank Indonesia's National Clearing System on the Money Supply (M2) in Indonesia. Data was obtained from the websites of Bank Indonesia and the Central Statistics Agency in 2011-2022. The research method used is the Error Correction Model (ECM). With the results of the study showing that in the long term, the use of credit cards, debit cards, and SKNBI has a significant effect on the amount of money supply (M2) in Indonesia. And in the short term, SKNBI also has a significant effect on the money supply (M2) in Indonesia. Meanwhile, the use of electronic money does not have a significant effect on the amount of money supply (M2) in the long or short term